2016
DOI: 10.1101/040105
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plant diversity accurately predicts insect diversity in two tropical landscapes

Abstract: Plant diversity surely determines arthropod diversity, but only moderate correlations between arthropod and plant species richness had been observed until Basset et al. (2012, Science 338: 1481-1484) finally undertook an unprecedentedly comprehensive sampling of a tropical forest and demonstrated that plant species richness could indeed accurately predict arthropod species richness. We now require a high-throughput pipeline to operationalize this result so that we can (1) test competing explanations for tro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…The dominance of dipterans in Malaise trap samples across the three anthropogenic forests was similar to previous findings, for example, Zhang et al (2016) reported that the collections from traps deployed in a tropical forest in southern mainland China comprised 43% dipterans ( n = 848). Similarly to Coleoptera and Lepidoptera, the proportion of Diptera was significantly affected by the interaction between forest type and maximum temperature.…”
Section: Discussionsupporting
confidence: 89%
“…The dominance of dipterans in Malaise trap samples across the three anthropogenic forests was similar to previous findings, for example, Zhang et al (2016) reported that the collections from traps deployed in a tropical forest in southern mainland China comprised 43% dipterans ( n = 848). Similarly to Coleoptera and Lepidoptera, the proportion of Diptera was significantly affected by the interaction between forest type and maximum temperature.…”
Section: Discussionsupporting
confidence: 89%
“…, Lewinsohn and Roslin ) and previous empirical outcomes both for elsewhere (Zhang et al. , Kemp and Ellis ) and for the region (Chown et al. ) demonstrating such a relationship (sites with vascular plant and high‐resolution temperature data, 18 SOIs).…”
Section: Methodsmentioning
confidence: 68%
“…Greater levels of arthropod biodiversity in native forest is not a surprise, given their more diverse vegetation structures and species compositions, which are well known to be positively correlated with arthropod diversity (Castagneyrol & Jactel, ; Haddad et al, ; Stork, Mcbroom, Gely, & Hamilton, ; Zhang et al, ), but the greater diversity and similarity of mixed plantations to native forests is somewhat surprising, especially as they mostly just comprise small‐scale monocultures, planted in checkerboard pattern. However, planting different tree species near each other not only provides more diverse vegetation per se but also, because the species vary in height and three‐dimensional structure, almost certainly allow greater sunlight penetration to the understorey, which in turn should result in greater availability of food and other resources.…”
Section: Discussionmentioning
confidence: 99%